Efficacy and safety of sublingual tablets of house dust mite allergen extracts: Results of a dose-ranging study in an environmental exposure chamber - Roux, Michel; Devillier, Philippe; Yang, William H.; Montagut, Armelle; Abiteboul, Kathy; Viatte, Agnès; Zeldin, Robert K. (Journal of allergy and clinical immunology, 2016)
In a natural field study, sublingual tablets of house dust mite (HDM) allergen extracts (STG320) were efficacious in treating HDM-associated allergic rhinitis. We sought to assess the efficacy and safety of 3 doses of STG320 in an environmental exposure chamber. In this randomized, double-blind study, adults with HDM-associated allergic rhinitis were given a daily sublingual tablet containing placebo or STG320 at a dose of 500IR, 300IR, or 100IR (IR, index of reactivity) for 6 months. Participants recorded their rhinitis symptoms during 4-hour HDM EEC challenges at randomization and months 1, 2, 4, and 6. The primary efficacy end point was the change from baseline to end of treatment in the area under the curve of the rhinitis total symptom score (ChBLAUCRTSS 0-4h). Differences from the placebo group were analyzed by analysis of covariance. Adverse events (AEs) and routine safety parameters were recorded. A total of 355 subjects were randomized to 1 of 4 groups: 500IR (n = 93), 300IR (n = 86), 100IR (n = 89), or placebo (n = 87). The least squares mean differences from placebo in ChBLAUCRTSS 0-4h for the 500IR, 300IR, and 100IR groups indicated a dose-dependent effect, with reductions in symptom scores of 33%, 29%, and 20%, respectively. The most frequent AEs were throat irritation and oral pruritus. There were no reports of anaphylaxis or reports consistent with severe laryngopharyngeal disorders and no use of epinephrine. AEs leading to premature discontinuations were more common in the 500IR group. A dose-dependent effect of sublingual HDM immunotherapy was demonstrated in this environmental exposure chamber study, supporting further development of this treatment.